2005
DOI: 10.1021/es048553n
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Recovery of Surface Waters Across the Northeastern United States from Reduced Inputs of Acidic Deposition:  1984−2001

Abstract: Changes in lake water chemistry between 1984 and 2001 at 130 stratified random sites across the northeastern United States were studied to evaluate the population-level effects of decreases in acidic deposition. Surface-water SO4 2- concentrations decreased across the region at a median rate of −1.53 μequiv L-1 year-1. Calcium concentrations also decreased, with a median rate of −1.73 μequiv L-1 year-1. This decrease in Ca2+ retarded the recovery of surface water acid neutralizing capacity (Gran ANC), which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 21 publications
2
64
2
Order By: Relevance
“…Sugar maple, which comprises ∼35% of the W1 biomass and has high Ca requirements (20,26), increased in foliar Ca between 1999 and 2002, followed by stable but elevated Ca concentrations thereafter (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugar maple, which comprises ∼35% of the W1 biomass and has high Ca requirements (20,26), increased in foliar Ca between 1999 and 2002, followed by stable but elevated Ca concentrations thereafter (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…The critical role of Ca in forests has highlighted the need to understand better the consequences of available soil Ca depletion. Acid deposition has caused rates of Ca leaching to far exceed rates of replenishment through weathering and atmospheric deposition, making soil Ca loss a threat to long-term forest vitality in regions prone to acid deposition (13,(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…In contrast, stream water draining W6 is characterized by low ANC, showing that this small, high-elevation watershed with shallow surficial deposits and flashy hydrology is highly sensitive to acidic deposition, particularly when compared to other watersheds studied in the Northern Forest that are generally larger in area (ranging to 3000 ha) and lower in elevation. It is noteworthy that the rates of increase in ANC at the HBEF are comparable and indicative of the widespread recovery of the Northern Forest in response to decreases in acid deposition (Kahl et al 2004, Warby et al 2005. This relatively uniform rate of recovery seems consistent with the observation that the magnitude of historical acidification (i.e., estimated loss of ANC from 1850 to present) in streamwater at the HBEF (Gbondo-Tugbawa and Driscoll 2003) is comparable to values projected across the Northern Forest (Chen andDriscoll 2005a, Zhai et al 2008).…”
Section: Acid Deposition Effectsmentioning
confidence: 97%
“…The latter is based upon regional lake-watershed surveys carried out by the U.S. Environmental Protection Agency Direct/Delayed Response Project (DDRP; Adirondack, Central New England, and Northern New England subregions; Warby et al 2005). We show data for two stream reaches in W6: at the headwaters of the drainage (732 m) and at the gaging station (541 m, elevation, 13.2-ha catchment area; Fig.…”
Section: Acid Deposition Effectsmentioning
confidence: 99%
“…Acid neutralizing capacity and pH of surface waters in this region have increased slightly since these laws were enacted (Warby et al 2005). However, in a survey of 189 small streams in the western Adirondack Mountain region, Lawrence et al (2009) found that 30% remain affected by episodic acidification.…”
Section: Introductionmentioning
confidence: 99%